VD_FINDINFO HC / 2018 / 15 vom 7. Dezember 2017 - VD Tribunal cantonal (2017)
EXPULSION DE LOCATAIRE, BAIL À LOYER, CAS CLAIR | 257d CO, 112 al. 1 CPC (CH), 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH)